Preparation, biological & cheminformatics-based assessment of N2, N4-diphenylpyrimidine-2, 4-diamine as potential Kinase-targeted antimalarials. (15th September 2021) - Toviwek, Borvornwat; Phuangsawai, Oraphan; Konsue, Adchatawut; Hannongbua, Supa; Riley, Jennifer; Mutter, Nicole; Anderson, Mark; Webster, Lauren; Hallyburton, Irene; Read, Kevin D; Gleeson, M. Paul
Graphical abstract: Highlights: 28 new 2, 4 diamino-pyrimidines have been tested against the Plasmodium falciparum . Cytotoxicity, Clint, logD7.4, PAMPA Pe and aqueous solubility have been assessed. 13 was identified as a potent antimalarial (IC50 = 0.42 µM) with good selectivity. 11 was µM potent with low logD7.4 (2.27) and good solubility 124 µg/ml, Abstract: Twenty eight new N 2, N 4 -diphenylpyrimidine-2, 4-diamines have been prepared in order to expand our understanding of the anti-malarial SAR of the scaffold. The aim of the study was to make structural modifications to improve the overall potency, selectivity and solubility of the series by varying the anilino groups attached to the 2- and 4-position. We evaluated the activity of the compounds against Plasmodium falciparum ( Pf ) 3D7, cytotoxicity against HepG2, % inhibition at a panel of 10 human kinases, solubility, permeability and lipophilicity, and human and rat in vitro clearance. 11 was identified as a potent anti-malarial with an IC50 of 0.66 µM at the 3D7 strain and a selectivity (SI) of 40 in terms of cytotoxicity against the HepG2 cell line. It also displayed low experimental logD7.4 (2.27), reasonable solubility (124 µg/ml), good metabolic stability, but low permeability. A proteo-chemometric workflow was employed to identify putative Pf targets of the most promising compounds. Ligand-based similarity searching of the ChEMBL database led to the identification of most probable human targets. These were then used as input for sequence-based searching of the Pf proteome. Homology modelling and molecular docking were used to evaluate whether compounds could indeed bind to these targets with valid binding modes. In vitro biological testing against close human analogs of these targets was subsequently undertaken. This allowed us to identify potential Pf targets and human anti-targets that could be exploited in future development.